Adsorption of Metanil Yellow Dye with Sugarcane Bagasse (Saccharum offinarum L.) Activated Carbon Modified with Cetyl Trimethyl Ammonium Bromide (CTAB) Surfactant - Sasi Kirana; Ratna Sari Dewi (Universitas Negeri Medan, 2025)
Environmental pollution caused by textile industry wastewater containing synthetic dyes such as Metanil Yellow has become a serious concern due to its carcinogenic nature. This study aims to determine the adsorption capacity of activated carbon derived from sugarcane bagasse waste (Saccharum officinarum L.), which was activated using Potassium Hydroxide (KOH) and modified with the cationic surfactant Cetyl Trimethyl Ammonium Bromide (CTAB). The activated carbon was produced through carbonization at 500 °C for 2 minutes, followed by chemical activation using 5N KOH and surface modification with CTAB. FTIR characterization showed spectral changes with the appearance of new functional groups such as –CH₂ vibrations (2961 and 2849 cm⁻¹), –C–N (1020 cm⁻¹), and quaternary ammonium –N⁺(CH₃)₃ (1470 cm⁻¹), indicating successful interaction of CTAB molecules on the carbon surface. The adsorption results showed that optimum conditions were achieved at an adsorbent mass of 1.5 grams, Metanil Yellow concentration of 25 ppm, and a contact time of 30 minutes, with an adsorption efficiency of 94%.